Determinación de las concentraciones del material particulado y , en la vía e35 intercambiador Pujilí - Latacunga período 2019-2020. - Rivera Garcés, Mariela Alejandra (2020)
The purpose of this researching was to determine the concentrations of the Particulate Material 10 and 2,5in E35 Pujilí- Latacunga road, generated by the influence of traffic junk. To this end, four objectives were set: characterize the area of study, monitor the amount of particulate material, generate a database which was compared with the current Ministerial Agreement 097-A and propose proposals for mitigation and control. For this purpose, two sampling points were determined where the monitoring was carried out, each point for 48 hours, 24 for 10 and 24 for 2,5, through the E-BAM equipment , under the established norms that allowed monitoring and generating a data base in a precise manner, which is fundamental to determine the state of contamination in the area of study. Once the data was obtained, it was compared with the Current Regulations 097-A, which indicates that for 10 it is 100 3⁄and for 2,5 it is 50 3⁄. The data shows that they are within the maximum permissible limits, despite the fact that in some hours there was a rise in concentrations due to the days of the fair, the first point being 36 3 ⁄ at 19:00; 20:00 with a value of 33 3⁄ at 17:00 for 10 and 30 3⁄ at 0:00 for 2,5 , at the second point 40 3⁄ at 17:00 for 10 and 17 3⁄ ; 0 3⁄ at 7:00 and 4:00 for 2,5. Therefore, three prevention measures were proposed, such as creating protective barriers with natural species and vehicle control at the time of registration to improve air quality and above all the health of the people living in the sector.